Trust Issue Analysis: Psycholinguistic Study In Sherine Abdel Wahab Garh Tany's Song Albums - Sa'baniyah, Hanania Hanum; Zawawi, Moh (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Abstract This research explores the phenomenon of trust issue in a romantic relationship through the analysis of song lyrics in the album Garh Tany performed by Sherine Abdel Wahab. The purpose of this research is to represent the trust issue phenomenon contained in the lyrics of Sherine's song on the album Garh Tany. The data was collected through the analysis of lyric text from three songs contained in the Garh Tany album, namely Shabri Aleel, Eh eh, and Garh Tany, then analyzed using the content analysis method to identify themes, patterns, and meanings. The results of this reseach show that the phenomenon of trust issues contained in the three song lyrics describes trust issues in a relationship caused by a bad experience experienced by one of the partners, some of the bad experiences found include betrayal, disappointment, abandonment, reflection and acceptance. Betrayal often appears as a major theme, where the partner feels betrayed and it is difficult to trust again. Disappointment is also often found because it reflects feelings of being hurt due to unfulfilled expectations. Some of the bad experiences experienced by one of the couples above have their own impacts, namely, experiencing overthingking, where the individual constantly thinks about the bad events or experiences he experiences; disturbances in social relationships, where individuals have difficulty interacting with others; and depression as a heavy emotional impact due to loss of trust. Asbtrak Penelitian ini mengeksplorasi fenomena trust issue dalam suatu hubungan percintaan melalui analisis lirik lagu dalam album Garh Tany yang dibawakan oleh Sherine Abdel Wahab. Tujuan penelitian ini adalah untuk merepresentasikan fenomena trust issue yang terdapat di dalam lirik lagu Sherine pada album Garh Tany. Data dikumpulkan melalui analisis teks lirik dari tiga lagu yang terdapat dalam album Garh Tany yaitu Shabri Aleel, Eh eh, dan Garh Tany, kemudian dianalisis menggunakan metode analisis konten untuk mengidentifikasi tema, pola, dan makna. Hasil penelitian ini menunjukan bahwa fenomena trust issue yang terdapat dalam ketiga lirik lagu tersebut menggambarkan trust issue dalam sebuah hubungan yang disebabkan karena adanya pengalaman buruk yang dialami oleh salah seorang pasangan, beberapa pengalaman buruk yang ditemukan meliputi adanya pengkhianatan, kekecewaan, pengabaian, refleksi dan penerimaan. Pengkhianatan sering muncul sebagai tema utama, dimana pasangan merasa dikhianati dan sulit untuk mempercayai kembali. Kekecewaan pun juga sering ditemukan sebab mencerminkan perasaan terluka akibat harapan yang tidak terpenuhi. Dari beberapa pengalaman buruk yang dialami oleh salah seorang pasangan di atas memiliki dampak tersendiri, diantaranya yaitu, mengalami overthingking, dimana individu terus-menerus memikirkan kejadian atau pengalaman buruk yang ia alami; gangguan dalam hubungan sosial, dimana individu mengalami kesulitan untuk berinteraksi dengan orang lain; dan depresi sebagai dampak emosional berat akibat kehilangan kepercayaan.